2018
DOI: 10.18203/2349-3933.ijam20183129
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm production and its correlation with antibiotic resistance pattern among clinical isolates of Pseudomonas aeruginosa in a tertiary care hospital in north-east India

Abstract: INTRODUCTIONPseudomonas aeruginosa is an aerobic, motile, nutritionally versatile, gram negative bacteria. It is ubiquitous, human opportunistic pathogen and has implications on morbidity, mortality and healthcare costs both in hospitals and in the community.1 Infections caused by P. aeruginosa are frequently life-threatening and difficult to treat causing increased stay in hospital and even increased morbidity and mortality as it exhibits intrinsically high resistance to many antimicrobials and the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…The present study show, maximum biofilm-producing isolates recovered from specimens received from ICU (63.64%) compared to the ward (36.36%) and similar findings was shown in another study (83.3%) [2]. This could be possibly due to the ICU setup uses multiple medical devices for treatment and intervention of patient care although indwelling devices used widely in hospitals [24] and biofilm is known for colonizing these medical devices.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The present study show, maximum biofilm-producing isolates recovered from specimens received from ICU (63.64%) compared to the ward (36.36%) and similar findings was shown in another study (83.3%) [2]. This could be possibly due to the ICU setup uses multiple medical devices for treatment and intervention of patient care although indwelling devices used widely in hospitals [24] and biofilm is known for colonizing these medical devices.…”
Section: Discussionsupporting
confidence: 85%
“…This may be due to the widespread use of these easily available antibiotics without knowing the infection status. All isolates were susceptible to polymyxin-B and colistin like other studies [1,2,21].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Such variation within species would make it unreliable to establish a concentrate relationship on the biofilm formation and genus. Moreover, significant correlation was found between antibiotic resistance and biofilm formation in Pseudomonas aeruginosa [45,46] while other studies have found otherwise [47]. A study between P. aeruginosa from environmental and human sources observed significantly weaker biofilm formation and susceptibility to most antibiotics from environmental isolates as compared to human sources [48].…”
Section: Discussionmentioning
confidence: 99%